2004
DOI: 10.1534/genetics.104.032375
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Architecture of Flowering Time in Maize As Inferred From Quantitative Trait Loci Meta-analysis and Synteny Conservation With the Rice Genome

Abstract: Genetic architecture of flowering time in maize was addressed by synthesizing a total of 313 quantitative trait loci (QTL) available for this trait. These were analyzed first with an overview statistic that highlighted regions of key importance and then with a meta-analysis method that yielded a synthetic genetic model with 62 consensus QTL. Six of these displayed a major effect. Meta-analysis led in this case to a twofold increase in the precision in QTL position estimation, when compared to the most precise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
350
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 363 publications
(366 citation statements)
references
References 78 publications
11
350
1
2
Order By: Relevance
“…While the effect is relatively weak, this may be explained by the fact that many genes appear to affect flowering time in maize (Chardon et al 2004). A role in flowering time has also been demonstrated for LFY in Arabidopsis with a dosage series experiment that clearly demonstrated that increasing functional LFY copies results in a quantitative dosage-dependent acceleration of flowering time analogous to what we observed in maize (Blázquez et al 1997).…”
Section: Discussionsupporting
confidence: 64%
“…While the effect is relatively weak, this may be explained by the fact that many genes appear to affect flowering time in maize (Chardon et al 2004). A role in flowering time has also been demonstrated for LFY in Arabidopsis with a dosage series experiment that clearly demonstrated that increasing functional LFY copies results in a quantitative dosage-dependent acceleration of flowering time analogous to what we observed in maize (Blázquez et al 1997).…”
Section: Discussionsupporting
confidence: 64%
“…Early and recent reviews on the genetics of maize flowering time recognized the chromosome region bin 8.05, bearing Vgt1, as a ''hot spot'' for flowering-time QTLs and genes (3,20). Although the genetic resolution reported in those studies was never at the gene level, it is likely that at least some of the reviewed QTLs were due to allele segregation at Vgt1.…”
Section: Discussionmentioning
confidence: 99%
“…In systems where more QTL studies have been conducted, more formal meta-analyses and computation of a composite map combining several densely genotyped panels may further improve the confidence of QTL/candidate gene colocalization and thus also improve the efficiency of this approach (Arcade et al 2004;Chardon et al 2004). Several observations suggest that genetic hitchhiking is a concern that impacts how effectively improvement loci can be identified, however.…”
Section: Discussionmentioning
confidence: 99%